Psychometric properties of the Beliefs about Medicine Questionnaire–adjuvant endocrine therapy (BMQ-AET) for women taking AETs following early-stage breast cancer. Issue 2 (November 2017) - Brett, Jo; Hulbert-Williams, Nick J; Fenlon, Deborah; Boulton, Mary; Walter, Fiona M; Donnelly, Peter; Lavery, Bernadette; Morgan, Adrienne; Morris, Carolyn; Horne, Rob; Watson, Eila
This study evaluated the Beliefs about Medicine Questionnaire to explore adherence to adjuvant endocrine therapy after treatment for breast cancer (BMQ-AET). Factor structure of the BMQ-AET was explored alongside internal consistency, convergent validity and acceptability. The BMQ-AET Specific Scale fitted the original 10 item model. Internal consistency of the BMQ-AET was much improved compared to the original BMQ and convergent validity showed predicted direction of correlation, although correlation with BMQ-AET concerns scale was low. Acceptability was good. The evaluation of the BMQ-AET is encouraging, and could facilitate future research around adherence to AET.